2019
DOI: 10.5194/hess-23-5069-2019
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and structure of microtopography implies autogenic origins in forested wetlands

Abstract: Abstract. Wetland microtopography is a visually striking feature, but also critically influences biogeochemical processes at both the scale of its observation (10−2–102 m2) and at aggregate scales (102–104 m2). However, relatively little is known about how wetland microtopography develops or the factors influencing its structure and pattern. Growing research across different ecosystems suggests that reinforcing processes may be common between plants and their environment, resulting in self-organized patch feat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 79 publications
(96 reference statements)
1
33
0
Order By: Relevance
“…That is, wetland microtopography can result from feedbacks among hydrology, vegetation, and soil processes that induce soil elevation divergence into two modes: (1) a high-elevation mode (hummocks) and 2a low-elevation mode (hollows) (Rietkerk et al, 2004;Eppinga et al, 2008;Heffernan et al, 2013). In previous work, we observed clear microtopographic patterns that we propose arise from these types of ecohydrological feedbacks (Diamond et al, 2019). If these microtopographic patterns are in fact a result of proposed ecohydrological feedbacks, we therefore expect there to be concordant microtopographic differences in vegetation and soils.…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…That is, wetland microtopography can result from feedbacks among hydrology, vegetation, and soil processes that induce soil elevation divergence into two modes: (1) a high-elevation mode (hummocks) and 2a low-elevation mode (hollows) (Rietkerk et al, 2004;Eppinga et al, 2008;Heffernan et al, 2013). In previous work, we observed clear microtopographic patterns that we propose arise from these types of ecohydrological feedbacks (Diamond et al, 2019). If these microtopographic patterns are in fact a result of proposed ecohydrological feedbacks, we therefore expect there to be concordant microtopographic differences in vegetation and soils.…”
Section: Introductionsupporting
confidence: 54%
“…Importantly, the monotypic nature of black ash systems coupled to existential threats from the invasive emerald ash borer (Agrilus planipennis) has led to black ash being listed as critically endangered (Jerome et al, 2017), making the study of their ecology a timely matter. In a complementary study (Diamond et al, 2019) of black ash wetlands, we observed an evident hummock-hollow structure that was more pronounced at wetter sites. Here, we further investigate the ecological importance of black ash microtopography and ask the following question: to what extent do the integrated controls of water table regimes and microtopography determine spatial variation in vegetation and soil properties?…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations